Commuting a mundane journey - Gonzales, Erris; Cabangis, Benjamin; Olazo, Jonathan Emmanuel (Quezon City College of Fine Arts, University of the Philippines Diliman, 2017)
The purpose of this thesis is to explore the use of traditional and digital media simultaneously. Growing up, I was fascinated by digital media and techniques. For the work, my objective is to combine together with traditional techniques with reproduction and enhancement capabilities of digital media. As an alternative method in creating stained glass effect, it uses cheap materials such as acrylic sheet, glass paints and sticker paper for printing digital linear images. Using these materials, the work was about an autobiographical narrative of a college student who commutes from provincial home to school and vice versa every week, making it a mundane journey of her commuting experience.
Thesis (Bachelor of Fine Arts in Studio Arts)--University of the Philippines Diliman
Bibliography : leaves 25-26.
Keywords: Commuting college students; Digital media; Acrylic painting